Determinação de ecstasy e derivados anfetamínicos em amostras de urina utilizando-se cromatografia líquida de alta eficiência com detecção de ultravioleta e em comprimidos utilizando-se cromatografia em fase gasosa com detector de ionização de chama - Marcelo Carvalho Lasmar (2007)
The abusive amphetamine use and its derivatives have shown a dramatic increasing in the last years in diverse regions of the world and Brazil, namely the special use of ecstasy (MDMA). These drugs are easily synthetized and commercialized with extreme discretion, what it strengthens the necessity of the development of forms of identification of these substances. A simple method, of easy execution and low financial cost, is proposed for identification and quantification of MDMA and its main metabolite (MDA) in human urine samples performed by high performance liquid chromatography UV detector. Identification and quantification of MDMA and others amphetamines derivatives (MDA and MDE) in tablets were also performed using gas chromatography flame ionization detector. The amphetamines derivatives are eluted in adjusted time and resolution. The optimized methods have shown adequate linearity, precision, selectivity and robustness, besides being capable to detect the analytes even when present in very little amount, not only in urine but also in tablets, being thus suitable to be adopted as confirmatory methods in forensic laboratories.